Doxorubicin conjugated with nanodiamonds and in free form commit glioblastoma cells to heterodromous fates. (24th January 2019) - Chen, Zhuo; Wang, Chao; Li, Tong-Fei; Li, Ke; Yue, Yuan; Liu, Xin; Xu, Hua-Zhen; Wen, Yu; Zhang, Quan; Han, Min; Komatsu, Naoki; Xu, Yong-Hong; et al.
Aim: To mechanistically compare the effects of doxorubicin (DOX) and DOX conjugated with nanodiamonds (Nano–DOX) on human glioblastoma cells (GC).Materials & methods: GC viablity,  proliferation and activation of apoptosis and autophagy was assayed in response to DOX and Nano–DOX. Expression and release of HMGB1 were measured and its role in apoptosis and autophagy probed in response to DOX and Nano–DOX.  Results: DOX induced apoptosis in GC while Nano–DOX induced autophagy. Inhibition of autophagy in Nano–DOX-treated GC promoted apoptosis. DOX suppressed the emission of HMGB1 while Nano–DOX stimulated HMGB1 emission which was attenuated when autophagy was repressed. Blocking of HMGB1 emission mitigated autophagy and enhanced apoptosis in Nano–DOX-treated GC. Exogenously administered HMGB1 promoted autophagy and protected against apoptosis in both Nano–DOX-treated GC and DOX-treated GC.Conclusions: Nano–DOX is a potent autophagy activator as opposed to DOX as an apoptosis inducer. Nano–DOX initiates a mutual reinforcement loop between autophagy and HMGB1 in GC and thereby protects GC against apoptosis.